A construção do mercado de E-books no Brasil : uma análise por meio de práticas de marketing - Medeiros, Juliana (2013)
This research presents a study of the electronic publishing market construction in Brazil, through an analysis on how the market is constructed, considering all agents involved directly and indirectly, and practices (exchange, normative and representational) to formatting these market (KJELLBERG; HEGELSSON, 2007). For this, is necessary move away from the conventional literature that represents the market as an absent and non-existent, presenting mainly ways to connect organizations to consumer (ARAUJO et al., 2010) and is supported by the literature of Marketing-making. To illustrate the approach, the study presented empirical evidence of such market, describing how it is built from introduction the e-books. These data were submitted to the NVIVO software 10 which aided in interpreting the data and the theoretical connection. We used qualitative research method, through content analysis of the data collected by observation and interviews. The main findings were: 1) exchange practices: reposition the market through individual marketing strategies, appreciating the values measured by the local culture and reconstruction of the marketing mix, 2) representational practices: a spectacle of reality by means of stimulating images and statistics that represent how was characterized the electronic publishing market, mainly in the Bienal do Livro, 3) normative practice: role in government to ensure the interests of the group and attempt to provide agential capacity to market players, so that they could represent the whole market before the policy, ensuring the interest agential the entire network. Each practice influences the other practice separately. Among the managerial implications, we emphasize: 1) create satisfying shopping experience, 2) representations and joint efforts with relevant performance practices to assist news dissemination; 3) act in public sphere to create regulations for the market. Among the contributions to the scientific field, we emphasize: 1) expanding the possibilities for analysis and explanations on marketing, since the conventional literature has shown the discipline as a functional department within the organization.